GAMBARAN RADIOLOGIS PADA OCCULT PNEUMOTHORAKS - Satya Putra, Putu Aditha; Laksminingsih, Nyoman Srie (E-Jurnal Medika Udayana; vol 2 no1 (2013):e-jurnal medika udayana)
Pneumothorax is a recognized cause of death in chest wall trauma. Radiological examination is the key factor to establish the existence of a pneumothorax. Occult pneumothorax is pneumothorax that undiagnosed clinically and with thoracic x-ray, but it can be tolerated while other more urgent trauma. Occult pneumothorax can be detected by CT (Computed tomography). Occult pneumothorax may progress to tension pneumothorax in certain circumstances. Missing in diagnosed pneumothorax will cause death. This literature will discuss radiological examination for diagnosing, early detection, and management of occult pneumothorax. If thoracic x-ray examination did not reveal the occult pneumothorax, it can be dangerous if existence of pneumothorax was not known. In this case, the examination of thoracic CT-Scan is gold standard for determining the presence of occult pneumothorax and can provide appropriate care.
Keywords: Pneumothorax, occult pneumothorax, CT-Scan thorax